Leaflet Matematika Perbandingan Berbasis Hukum Waris Al-Qur’an: Analisis Kepraktisan dan Efektivitas - Meldi, Nadya Febriani; Sugiatno, Sugiatno; Agung Hartoyo (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
Ethnomathematics-based learning grounded in the Qur’an is highly essential for religious-based schools as a strategic step to optimize the learning process. One promising approach is the development of Qur’an-integrated mathematics teaching materials. Unfortunately, many of these developments end after a single trial, despite the necessity of periodic and systematic evaluations. This study aims to continue the previous development of a mathematics leaflet sourced from the Qur’an and enhanced with QR code integration, by further examining its effectiveness and practicality. This study employed a quantitative research method, using a set of four validated test items. The content of the inheritance problem used in the test was adjusted to align with the learning outcomes in the fiqh subject, particularly in the topic of inheritance distribution. In addition to the test, the instruments used to assess practicality included an observation sheet and a student response questionnaire. Students who are the subjects are at the junior high school / equivalent level, precisely in class VII. In terms of effectiveness, the test results showed an average class score of 78.3, with 100% of students achieving the minimum mastery criteria (KKM), categorized as